Between miniature and actuality: an askos from Tarquinia (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
New evidence from a sealed context in Tarquinia (mid-II century B.C.) of an askos belonging to the Ruvfies Group with atranes stamp allows some observations with regard to the use of sigma instead of the usual san. The Southern connotation of the writing stands out within the known record that traditionally locates the production of such askoi in the Northern Etruscan region (Perugia), based on onomastic and epigraphic analyses. Such epigraphic evidence opens up to new speculations regarding the relationship between production and commission and the different production methods from the various artisan workshops.
Keywords: Askoi; Atranes; Tarquinia; Ruvfies Group